Kiprah Pengajar Madrasah Dalam Membentuk Karakter Ikhsani Siswa pada Era Digital - Safuroh Safuroh; Wahyu Hidayat; Wasehudin Wasehudin (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
The purpose of this writing is to find out the progress of madrasa teachers as educators in producing the behavior habits of students who are formed in an ikhsani character in dealing with the demands of the times in the digital era. In this study the method used was a qualitative case study method, while the method of collecting information was carried out by observation, documentation and interviews. Information analysis techniques by reducing, presenting, and concluding. The objects in this study were students and teachers at MTs Al-Khairiyah Badamusalam.The results of this study indicate that the role and strategy of the madrasa teacher applied at MTs Al-Khairiyah Badamusalam Serang City is very large in familiarizing students' spiritual character, this is indicated by the good character of students, but a small number of students still have bad character. Therefore, teachers must optimize their roles and strategies in teaching and guiding students. In order for these activities to be implemented optimally, there is a need for maximum guidance and supervision from teachers, especially PAI teachers and the need for good coordination and cooperation from related parties, namely student guardians, the community and the government Keywords: The gait of the teacher, forming the ikhsani chara